Alternatives for Rehabilitation of Cleft Patients With Severe Maxillomandibular Discrepancy. Issue 3 (May 2015) - Alves, Michelly Lima Moro; Lopes, José Fernando Scarelli; Lopes, Mônica Moraes Waldemarin; Pinto, João Henrique Nogueira; Soares, Simone
<x xml:space="preserve">Abstract</x> Abstract Rehabilitation of cleft patients is a process that occurs from birth to adult life and involves a team of many professionals. Reconstructive plastic surgery, despite its functional and aesthetic benefits to the patient, can restrict the normal anterior displacement that occurs in the growth of the maxilla, which, in turn, can lead to a concave profile that requires correction. This study aimed to demonstrate an alternative rehabilitation treatment for cleft patients who have severe maxillomandibular discrepancy and choose not to undergo orthognathic surgery. A retrospective review and case reports of rehabilitation treatment of cleft patients were performed, with an emphasis on prosthetic rehabilitation without orthognathic surgical procedures. Prosthetic rehabilitation is a fast and reversible option for cleft patients that provides facial harmony and facilitates the reintegration of these patients into society.